2010
DOI: 10.1021/ma902247y
|View full text |Cite
|
Sign up to set email alerts
|

A PALS Contribution to the Supramolecular Structure of Poly(l-lactide)

Abstract: Positron annihilation lifetime spectroscopy (PALS) was conducted to follow the evolution of free volume during crystallization of PLLA at 100°C. A finite lifetime distribution of three components was used to fit the PALS spectra. The analysis of the longest lifetime component (τ 3 ) indicates that the free volume distribution evolves during crystallization by increasing the number of holes yet decreasing their size; moreover, the free volume fraction increased during crystallization. Following the evolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 61 publications
4
55
0
2
Order By: Relevance
“…(X MA ) and rigid amorphous phases (X RA ) were determined according to a previously reported procedure (Del Rio et al, 2010) with the next equations…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…(X MA ) and rigid amorphous phases (X RA ) were determined according to a previously reported procedure (Del Rio et al, 2010) with the next equations…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…One reason might be that PLA seems to have lower oxygen solubility compared to PET [4]. Del Rio et al [41] studied very recently the evolution of free volume in crystallized PLLA with the help of Positron Annihilation Lifetime Spectroscopy (PALS) measurements. They observed an increase in free volume upon annealing which they located primarily inside the RAF.…”
Section: Gas Barrier Propertiesmentioning
confidence: 99%
“…The free volume theory predicts that diffusion is dominated by the scarcity of free volume and that specific molecular interactions are of secondary importance, particularly in the case of poorly interacting molecules as it is the case in the present system. An ''opener'' [41] structure might thus imply higher connectivity in order to allow transport [42]. Basically speaking, more small voids are more efficient than some large ones.…”
Section: Gas Barrier Propertiesmentioning
confidence: 99%
“…The RAF is the intermediate phase connecting the crystalline phase to the mobile amorphous fraction (MAF) [23]. The RAF constitutes a dedensified amorphous phase [24] because of geometrical constraints preventing structure relaxation. Guinault et al [14] showed that the formation of RAF was favoured when PLA was crystallized from the glassy state in a'-form.…”
Section: Introductionmentioning
confidence: 99%